Comparing Male and Female Engineering Students' Perceptions, Problems and Task-Based Needs about Academic Listening - Mahboubeh Taghizadeh; Neda Mohabbati (Comparative Education Society of Iran ( CESIR), 2018)
This study aimed to investigate Engineering students' perceptions, problems, and preferred tasks about academic listening. The participants were 199 Iranian undergraduate students of Engineering at the Iran University of Science and Technology. The instruments were a questionnaire with 40 items and an interview with 3 open-ended items. Considering learners' attitudes, both male and female learners were aware of the importance of academic listening for their success and found listening comprehension exciting. With regard to problems, both male and female learners reported that insufficient vocabulary, speed of speech, poor quality of recordings, long texts, and unfamiliar topics were their major listening problems. The findings also revealed that listening to news reports, listening to academic interview, listening to academic discussion, listening to announcement, and listening to conversation were the male students' preferred tasks, while listening to academic interviews, listening to seminars and presentations, listening to academic discussion were the female students' preferred tasks.